Pendidikan dan Pelatihan Komunitas WKRI Ranting Birgitta untuk Peningkatan Kesehatan Rongga Mulut - Firstine Kelsi Hartanto; Rahmi Amtha; Trijani Suwandi; Komariah; Luki Astuti; Andri Sutanto; Caroline Septiani; Jacinda Jesslyn; Nikita Theodorus; Elisabeth Sudarmi; Indrayadi Gunardi (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
The oral cavity is a mirror of a person's health that can show local and systemic health problems. Dental and oral health problems, especially caries, periodontal disease, and cancer are reported as diseases and disorders in dental and oral health that are still experienced by the population in the world and Indonesia. It is known from a preliminary survey, that family members of WKRI community partner Ranting Birgitta have quite a lot of oral health problems but cannot freely come to the dentist for treatment during the pandemic. The aim of this community service was (1) to increase the knowledge about the problem of caries, bleeding gums, bad breath and the prevention (2) to increase the knowledge of causes and manifestations of various disorders that arise due to systemic medications and how to overcome them. The activity was carried out offline through the educational materials in the form of presentations, demonstrations, and posters to members of the WKRI community of Birgitta branches and guests, on February 5, 2023, at Grha St. Mikael, Kranji, Bekasi. A total of 43 people (32 participants and 11 PkM teams) participated in this activity. The pre-test and post-test results attended by 29 participants showed a significant increase in knowledge by 1.2 times (p<0.001) of the material presented, with an average pre-test score of 54.66 and 78.10 for the average post-test score. Overall, the activity went smoothly. It is highly suggested that similar activities can be held again with a wider scope of participants.